Book Review: Davidson, A.L. (1996). Making and molding identity in schools: Student narratives on race, gender, and academic engagement. - Katherine Goff (Networks: An Online Journal for Teacher Research, 1998)
Making and Molding Identity in Schools presents detailed case studies of six high school students to illustrate how racial and ethnic identities struggle against the school policies, discourses, and practices that work to reproduce social categories. Ann Locke Davidson also shows how some teachers and programs successfully challenge social categories. She expands on current social theories that link identity exclusively to cultural, ecomonic, and political forces by portraying how identities develop in ordinary, everyday activities that occur over time in different school settings. Some of the identities that the students learn prevent some of them from successfully engaging in practices valued by the school.